Wpływ twyrczości Łesi Ukrainki na strukturę i znaczenie dzieła literackiego “Grupy nowojorskiej” - Карабович, Тадей; Kаrаbоvych, Tаdеy (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглянуто вплив творчості Лесі Українки на структуру та зміст літературного обличчя Нью-Йоркської групи. У світлі українського літературознавства Нью-Йоркська група надихалася творчістю Лесі Українки. Модерністична поетеса своєю твор- чістю зробила значний вплив на літературнi твори українських емігрантів. Цей вплив вважається номінальною вартістю, тобто загальною вартістю літератур- ної нарації та внутрішньотекстових відносин, із прихованою в глибших шарах перспективою реінтерпретації. Цей вплив створився в українській літературі під кутом роздумів над літературною творчістю Лесі Українки. Він також відноситься і до літературної спадщини Нью-Йоркської групи, що розуміється як взаємодія спадщини української поетеси зламу XIX та XX ст. на емігрантів. The article describes the influence of Lesia Ukrainka on the structure and importance of the literary achievements of the New York Group. According to the critics of the Ukrainian literature the New York Group profited from the inspiration gathered from the works of Lesia Ukrainka. Her poetry proved a lasting influence on the activity of The Group, even though each member of it derived from it different inspiring elements. The unacknowledged reinterpretation of the Lesia Ukrainka’s work by The Group brought forward the values of her poetry for another generation. The achievement of the New York Group can, thus, be considered a bridge between the Nineteenth and Twentieth centuries for the continuity of Lesia Ukrainka presence in the Ukrainian literature. The “New York Group” was a Ukrainian and Ukrainian-inspired literary йmigrй group in the USA, and it became part of the canon of Ukrainian literature in the second half of the twentieth century. The members of the Group include Emma Andiievska, Roman Baboval. Bohdan Boychuk, Zhenia Vasylkivska, Vira Vovk, Patricia Nell Warren, Oleh Koverko, Yurii Kolomiiets, Mariia Revakovych, Bohdan Tymish Rubchak, Yurii Tarnavskyi and Marko Tsarynnyk.
The Influence of Lesia Ukrainka on the Creativity and Importance of the New York Group
Keywords: Леся Українка; Нью-Йоркська група; література; поезія; українська еміграція; номінальний вплив; Lesia Ukrainka; The New York Group; literature; poetry; Ukrainian emigration; influence